Antineoplastic Isoflavonoids Derived from Intermediate ortho‐Quinone Methides Generated from Mannich Bases. (17th February 2016) - Frasinyuk, Mykhaylo S.; Mrug, Galyna P.; Bondarenko, Svitlana P.; Khilya, Volodymyr P.; Sviripa, Vitaliy M.; Syrotchuk, Oleksandr A.; Zhang, Wen; Cai, Xianfeng; Fiandalo, Michael V.; Mohler, James L.; Liu, Chunming; Watt, David S.
Abstract: The regioselective condensations of various 7‐hydroxyisoflavonoids with bis( N, N ‐dimethylamino)methane in a Mannich reaction provided C‐8 N, N ‐dimethylaminomethyl‐substituted isoflavonoids in good yield. Similar condensations of 7‐hydroxy‐8‐methylisoflavonoids led to the C‐6‐substituted analogs. Thermal eliminations of dimethylamine from these C‐6 or C‐8 N, N ‐dimethylaminomethyl‐substituted isoflavonoids generated ortho ‐quinone methide intermediates within isoflavonoid frameworks for the first time. Despite other potential competing outcomes, these ortho ‐quinone methide intermediates trapped dienophiles including 2, 3‐dihydrofuran, 3, 4‐dihydro‐2 H ‐pyran, 3‐( N, N ‐dimethylamino)‐5, 5‐dimethyl‐2‐cyclohexen‐1‐one, 1‐morpholinocyclopentene, and 1‐morpholinocyclohexene to give various inverse electron‐demand Diels–Alder adducts. Several adducts derived from 8‐ N, N ‐dimethylaminomethyl‐substituted isoflavonoids displayed good activity in the 1–10 μm concentration range in an in vitro proliferation assay using the PC‐3 prostate cancer cell line. Abstract : Thermally generated ortho ‐quinone methides from Mannich bases of 7‐hydroxyisoflavones or from 8‐methoxymethyl‐ or 8‐hydroxymethyl 7‐hydroxyisoflavones trapped a variety of electron‐rich dienophiles to give various inverse electron‐demand Diels–Alder adducts in good yields. Selected adducts displayed good activity in a proliferation assay using the PC‐3 prostate cancer cells.